Proving the Equality of the Spaces Q_b^r (A),Q_b^l (A) and BL(X) where X is a Complex Banach Space - Al-Neima, Mohammed Th.; Mohammed, Amir A. (Iraqi Journal of Science, 2020)
Cabrera and Mohammed proved that the right and left bounded algebras of quotients and of norm ideal on a Hilbert space are equal to Banach algebra of all bounded linear operators on . In this paper, we prove that where is a norm ideal on a complex Banach space .